Virtual Instrumentation Programming and Psoc Embedded Design for Bearing Fault Detection: Uses Impulse Excitation Technique - J. Jayakanth, J; Chandrasekaran, M (International Journal of Engineering & Technology, 2018)
This paper describes, a novel innovative design for generating vibration signals in a bearing, which is in static mode not in dynamic mode like other usual measurements reported in literatures,Â for various types of bearing faults analysis supports users with a technique based on monitoring vibration signals. This paper reports the computed power spectrum from vibration signal clearly identifies the fault signature with its raise in amplitude. Hence, in an impulse excitation technique vibration analysis with computed power spectrum provides an efficient monitoring of fault in axle bearings in a short timing. Programmable System on Chip (PSoC) creator design and Virtual Instrument program written in LabVIEW, a graphical language, provides efficient implementation of impulse excitation technique possible in static test method in a minimal time.Â Â Â